TANGGUNG JAWAB DIREKSI TERHADAP PEMEGANG SAHAM ATAS PELANGGARAN PRINSIP KETERBUKAAN INFORMASI DI PASAR MODAL. - Nianzah, Raodha Putri; Maryano, Maryano; Widodo, Gatut Hendro Tri (LPPM Institut Pendidikan Nusantara Global, 2024)
This study examines the responsibilities held by the board of Directors of the company to shareholders in the context of violations of the principle of disclosure of information in the capital market. With a focus on the dynamics of the relationship between the board of directors and shareholders, this study analyzes the impact of violations of the principle of disclosure of information on shareholder confidence and the value of the company. The results of the study are expected to provide insight into the role of the board of directors in ensuring proper information disclosure, as well as highlighting relevant legal and regulatory aspects in maintaining the integrity of the capital market. This study uses the type of normative juridical research by analyzing legal materials sourced from legislation and realized with various references from literature review. The results of this study that in the context of Capital Markets, companies that go public get additional capital from the public stock buyers. Previously, shares were only owned by a certain number of people such as family, relatives, and friends. However, by going public, shares are issued and sold to the general public, creating independent shareholders whose motivation is more on making a profit. The principle of disclosure becomes important, realized through the preparation of a prospectus that must contain all the details and material facts, made clear, and accountable to the board of directors. Violation of the principle of openness by the board of Directors may result in sanctions, such as reprimand or dismissal from office, in accordance with Law No. 40 of 2007. At the General Meeting of shareholders (GMS), the board of directors must account for their actions, and the legal consequences may include dismissal and civil or criminal liability. This principle affirms the importance of integrity in maintaining transparency and trust in the capital market.